2016
DOI: 10.17795/jjhr-31170
|View full text |Cite
|
Sign up to set email alerts
|

Gonad Shielding for Patients Undergoing Conventional Radiological Examinations: Is There Cause for Concern?

Abstract: Background: Gonad shielding is one of the fundamental methods by which to protect reproductive organs in patients undergoing conventional radiological examinations. A lack of or inadequate shielding of the gonads may increase the exposure of these organs and result in malignancies future generations. Objectives: The aim of this study is to investigate the prevalence of gonad shielding in patients undergoing conventional radiological examinations and the availability of gonad shields and gonad shielding protoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 11 publications
2
11
0
Order By: Relevance
“…Similarly, bismuth shields could reduce radiation exposure by 17 to 62%, based on anatomical region and X-ray tube setup [18,27]. Although the effectiveness of shielding has been documented for some X-ray examinations, evidence showed that shielding tools are not available in some X-ray centers and if so, their use is frequently ignored [17,28]. Several studies have focused on the availability and use of shielding tools in diagnostic X-ray centers across the country and contradictory results been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, bismuth shields could reduce radiation exposure by 17 to 62%, based on anatomical region and X-ray tube setup [18,27]. Although the effectiveness of shielding has been documented for some X-ray examinations, evidence showed that shielding tools are not available in some X-ray centers and if so, their use is frequently ignored [17,28]. Several studies have focused on the availability and use of shielding tools in diagnostic X-ray centers across the country and contradictory results been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The low adherence rate of radiographers applying lead shields is reported to result from the complexity in identifying gonadal position in relation to surface landmarks and the risk of obscuring bony structures. 5,24,25 Our developed bismuth ovarian shield protects the ovaries, colon, and pelvis bone by covering the entire pelvic region. Because bismuth shields can be placed more easily without concern for obscuring diagnostic features, these developed shields are easier to use, especially in crowded and emergency radiology centres.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, shielding the gonads with 1-mm lead sheet has been common practice among radiographers since the 1950s. 5 However, positioning of such shields is frequently incorrect. This results in repeated examinations that consequently increase the total radiation dose.…”
Section: Introductionmentioning
confidence: 99%
“…X-ray field collimation has been also recognized as one of the most important factors influencing image quality and patient dose. According to the safety principle ALARA, radiographers have to limit radiation field to anatomical area of interest (15,16).…”
Section: Introductionmentioning
confidence: 99%